Physico-chemical Characteristics of Ground Water Quality in Koundampalayam Panchayat, Coimbatore District, Tamilnadu- India - S. Logaswamy, K. M. Remia (Recent Research in Science and Technology, 2010)
Present work was undertaken to analyse theÃ‚Â physical and chemical characteristics of the drinking water in the selected areas of Kavundampalayam Panchayat in Coimbatore.Ã‚Â 15 bore wells having different depth were selected for analysis (three zones with five stations each). Over all analysis explains that all the parameters showed higher values at II zone compared to other zones. Some of the parameters were found to be higher than the prescribed limits while other parameters were lower than the limits. No marked relationships were recorded among the parameters. The water quality of these zones will be degrading much in future. The major factors of the water quality deterioration appeared to be the lack of proper sanitation and protection of drinking water bodies.